2008
DOI: 10.5193/jee.31.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Are Challenge (Ropes) Courses an Effective Tool? A Meta-Analysis

Abstract: This study reports the results of a meta-analysis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 15 publications
2
51
0
3
Order By: Relevance
“…Ropes courses generally instill basic teamwork functions between students. In a recent meta-analysis, the second largest effect size (d = 0.62) was attributed to group dynamics and supported the notion that such programs allow individuals to learn how to work together (Gillis & Speelman, 2008). Goldenberg and Soule (2011) used means-end theory in a longitudinal study and found that years after the completion of their course, students still believed the most salient parts of their course included building community and creating opportunities for teamwork.…”
Section: Group Outcomesmentioning
confidence: 90%
“…Ropes courses generally instill basic teamwork functions between students. In a recent meta-analysis, the second largest effect size (d = 0.62) was attributed to group dynamics and supported the notion that such programs allow individuals to learn how to work together (Gillis & Speelman, 2008). Goldenberg and Soule (2011) used means-end theory in a longitudinal study and found that years after the completion of their course, students still believed the most salient parts of their course included building community and creating opportunities for teamwork.…”
Section: Group Outcomesmentioning
confidence: 90%
“…Research by Hattie et al (1997) found that outdoor education programmes with a clear focus on personal development have, on average, small to moderate positive impacts on self-esteem, self-concept and self-efficacy and that programmes without a self-development philosophy are inclined to have negligible impacts. There have been extensive studies and reviews of research on the effects of outdoor education on self-constructs (e.g., Cason & Gillis, 1994;Ewert, 1990Ewert, , 1991Gillis & Speelman, 2008;Hattie et al, 1997;Marsh et al, 1986aMarsh et al, , 1986bNeill, 2002). Meta-analytic research has shown that an outdoor experience can result in notable outcomes with respect to enhancing self-esteem and that they have particularly strong lasting effects (Cason & Gillis, 1994;Haney & Durlak, 1998;Hattie et al, 1997;Neill & Richards, 1998).…”
Section: Outdoor Education and The Development Of Selfmentioning
confidence: 99%
“…50) conclude that, 'improvements caused by some applications of outdoor adventure in dimensions of self-concept, locus of control and in socialisation with peers and adults are likely to contribute to the process of healthy adolescent development'. Gillis and Speelman (2008) offer a more recent meta-analysis of outdoor adventure challenge programmes. Their research has a more precise focus than earlier Downloaded by [Staffordshire University] at 06:11 05 October 2014…”
Section: Downloaded By [Staffordshire University] At 06:11 05 Octobermentioning
confidence: 99%
“…Across the literature, average eff ects of ropes course interventions on psychological outcomes (regardless of sample-type or variable of interest) have been reported at d = .45 (Gillis & Speelman, 2008). Some outcomes such as interpersonal dynamics have eff ect sizes greater than .60 (Gillis & Speelman, 2008).…”
Section: The Ropes Coursementioning
confidence: 99%